Achieving both high reversible and stable Zn anode by a practical glucose electrolyte additive toward high-performance Zn-ion batteries - Song, Ming; Zhong, Cheng-Lin (Rare metals, 2022)
Aqueous Zn-ion batteries (ZIBs) featuring safety, affordability and high energy density may provide a promising solution to the demand for better energy storage devices. ZIBs with high electrochemical performances rely on a stable and reversible Zn metal negative electrode. The side reactions such as the hydrogen evolution reaction (HER) at the anode-electrolyte interface are responsible for the low reversibility, and uneven Zn deposition/dissolution gives rise to the instability of Zn anode. Here, a facile and scalable method of regulating electrolytes has been proposed by Chao and his co-works through adding a low-cost, safe and environmentally-friendly electrolyte additive: glucose. Theoretical calculations and experimental studies reveal that the glucose not only suppresses side reactions by modulating the solvated shell of Zn 2+ but also homogenizes Zn deposition/dissolution through forming a special local absorption interface. This bi-functional electrolyte additive endows the Zn anode with both high reversibility and stability, which efficiently improves the performances of ZIBs. This work explores a promising electrolyte strategy for realizing the large-scale application of ZIBs.